2000
DOI: 10.1002/1097-4628(20001003)78:1<47::aid-app80>3.0.co;2-l
|View full text |Cite
|
Sign up to set email alerts
|

Novel routes to polyelectrolytes and reactive polymers via ROMP

Abstract: Various derivatives of norbornene and 7‐oxanorbornenedicarboxylic acid have been synthesized and polymerized via Ring Opening Metathesis Polymerization (ROMP). The introduction of tetrahydropyranyl moieties as protection groups opened a way for the synthesis of polyelectrolytes through well‐defined transition metal alkylidene catalysts that are usually deactivated by reactions with acidic protons. The incorporation of methacrylate groups in the polycarboxylic acids was achieved either by copolymerization of me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…1 H NMR (CDCl3): δ ) 7.28-7.12 (m, 10 H, SPh), 6.80 (s, 1H, ArH), 6.69 (s, 2H, ArH), 6.11 (m, 2H, CHdCH), 4.07 (t, J ) 6.6 Hz, 2H, CH2O), 4.00 (s, 4H, CH2S), 3.82 (t, J ) 6.6 Hz, 2H, CH2O), 3.03 (m, 1 H), 2.90 (m, 1H), 2.21 (m, 1H), 1.91 (m, 1H), 1.75-1.58 (m, 5H), 1.54 (m, 1H), 1.51 (m, 1H), 1.46-1.19 (m, 14H). 13 11-Bromoundecyl ester 7 (1.6 g, 0.004 36 mol), hydroxypyridine 9 (1.057 g, 0.004 24 mol), and Cs 2CO3 (1.6 g, 0.0049 mol) were stirred in 80 mL of acetone at reflux for 12 h. The suspension was filtered, the solvent evaporated, and the residue purified by column chromatography (SiO 2, eluant: 1:1 hexanes/ethyl acetate) to afford pure 11 (2.24 g, 100%) as a colorless, viscous oil that crystallized as fine needles after several days. 1 (12).…”
Section: Exo-bicyclo[221]hept-5-ene-2-carboxylic Acid 11-(35-bis(phen...mentioning
confidence: 99%
See 1 more Smart Citation
“…1 H NMR (CDCl3): δ ) 7.28-7.12 (m, 10 H, SPh), 6.80 (s, 1H, ArH), 6.69 (s, 2H, ArH), 6.11 (m, 2H, CHdCH), 4.07 (t, J ) 6.6 Hz, 2H, CH2O), 4.00 (s, 4H, CH2S), 3.82 (t, J ) 6.6 Hz, 2H, CH2O), 3.03 (m, 1 H), 2.90 (m, 1H), 2.21 (m, 1H), 1.91 (m, 1H), 1.75-1.58 (m, 5H), 1.54 (m, 1H), 1.51 (m, 1H), 1.46-1.19 (m, 14H). 13 11-Bromoundecyl ester 7 (1.6 g, 0.004 36 mol), hydroxypyridine 9 (1.057 g, 0.004 24 mol), and Cs 2CO3 (1.6 g, 0.0049 mol) were stirred in 80 mL of acetone at reflux for 12 h. The suspension was filtered, the solvent evaporated, and the residue purified by column chromatography (SiO 2, eluant: 1:1 hexanes/ethyl acetate) to afford pure 11 (2.24 g, 100%) as a colorless, viscous oil that crystallized as fine needles after several days. 1 (12).…”
Section: Exo-bicyclo[221]hept-5-ene-2-carboxylic Acid 11-(35-bis(phen...mentioning
confidence: 99%
“…[7][8][9] Current norbornene functionalization strategies are based primarily upon elaboration of esters (2) synthesized as an 80:20 endo/exo isomeric mixture via the Diels-Alder reaction of cyclopentadiene and asymmetric dienophiles. 7,[10][11][12][13][14][15][16][17][18] Our research, directed toward the synthesis of a "universal" polymer backbone through the use of functionalized norbornenes possessing metalcoordination or hydrogen-bonding recognition motifs, has revealed limitations to this methodology. [19][20][21] Polymerization of some elaborately functionalized derivatives of monomer 2 where R ) a tethered pincer complex or a diaminopyridine recognition unit with catalyst 4 requires elevated temperatures and prolonged reaction times at low monomer-to-initiator stoichiometries ([M]:[I]).…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that carboxylic acid group in norbornene will reduce the reactivity of ROMP catalyst [22]. As a result, PNB with carboxylic acid groups could not be obtained directly from ROMP of 5-norbornene-2-carboxylic acid.…”
Section: Methodsmentioning
confidence: 99%
“…However, it has been reported that some functional groups such as hydroxyl and carboxylic groups would decrease the reactivity of the catalysts used for ROMP [22]. As a result, PNBs with those functional groups should be obtained via alternative methods.…”
Section: Introductionmentioning
confidence: 99%
“…28 Search for an orthogonally polymerizable difunctional monomer led us to investigate 5-norbornene-2-methylene methacrylate (N) since the norbornene group can be polymerized by ring opening metathesis polymerization (ROMP) without reaction of the pendant methacrylate. [29][30][31][32] Telechelic polymers with reactive end-groups can be generated by including an acyclic monounsaturated chain transfer agent (CTA) during the ROMP of cyclic olefins, 33 and an array of ABA triblock copolymers are accessible by using appropriately functionalized CTAs. For example, CTAs with functionalities appropriate for atom-transfer radical polymerization (ATRP), 34,35 reversible addition-fragmentation chain transfer (RAFT) 36 polymerization and hydroxyl-telechelic olefin macroinitiators [37][38][39][40][41][42] for ring-opening transesterification polymerization (ROTEP) of cyclic esters 26,43,44 have been reported.…”
Section: Plcnl Block Copolymersmentioning
confidence: 99%